Historical and Contemporary Review of Role of Commercial Banks In India: Examining the Role of Commercial Banks in Providing Financial Services to the Rural Poor in India (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Thispaper briefly traces the historical and contemporary imperatives to providefinancial services to the rural poor in India and the institutional responsesto the same.